Finely tuned eye movements enhance visual acuity - Janis Intoy (Nature Portfolio, 2020)
Humans are normally not aware that their eyes are always in motion, even when attempting to maintain steady gaze on a point. Here the authors show that these small eye movements are finely controlled and contribute more than two lines in a standard eye-chart test of visual acuity.